Investigating Tensile Strength in SLA 3D Printing Enhancement Through Experimentation and Finite Element Analysis - Siwasit Pitjamit; Norrapon Vichiansan; Parida Jewpanya; Pinit Nuangpirom; Pakpoom Jaichomphu; Komgrit Leksakul; Pattarawadee Poolperm (Journal of Applied Engineering and Technological Science (JAETS), 2024)
This study aims to optimize tensile strength in Stereolithography (SLA) 3D printing by investigating the effects of print orientation and layer orientation on mechanical properties. Employing a multilevel factorial design, we systematically analyzed various print andlayer orientations using both experimental and computational methods. The experimental component, performed with an Instron 5566 machine, identified a print orientation of 22.5 degrees and side orientations as optimal, achieving a tensile strength of 72.01 MPa. Computational simulations using ANSYS software supported these findings, showing a close correlation between experimental and simulated results. This research not only advances theoretical understanding of SLA 3D printing processes but also offers practical insights for optimizing tensile strength in manufacturing applications. By integrating experimental and finite element analysis (FEA) results, which predicted a maximum stress of 71.97 MPa under a 686 N load, the study contributes valuable knowledge for enhancing additive manufacturing practices and informs future research on parameter optimization